1983
DOI: 10.1136/bjo.67.4.249
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein angiography and fluorophotometry of the iris in pseudoexfoliation of the lens capsule.

Abstract: SUMMARY Fluorescein iris angiography and fluorophotometry were performed on a series of 9 patients with bilateral and 11 with unilateral pseudoexfoliation, 12 bilateral aphakes with pseudoexfoliation, and 7 unilateral aphakes with bilateral pseudoexfoliation. Angiography showed a loss of radial iris vessels, a heavy leak of fluorescein from the pupil margin, progressive neovascularisation of the outer 2/3 of the iris, and less constantly a network of fine new vessels in the inner '/3 of the iris stroma. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
6

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 13 publications
1
34
0
6
Order By: Relevance
“…The shades of histological findings correlate with the different expressions of the fluorangiographic features, which have been described as hypoperfusion, microneovascularisation, and anastomotic vessels vessels (Vannas 1969(Vannas , 1972Kottow 1979;Brooks & Gillies 1983. IICGA has been shown to improve the imaging of the iris vascular pattern in diabetic iridopathy and iris arteriovenous communications, thanks to a better penetration of the infrared wavelengths through the iris pigmentation, as well as a minimal dye-leakage in relation to the strong protein binding of the dye and the consequent large protein complex (Parodi et al 1995(Parodi et al , 1996(Parodi et al , 1998.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The shades of histological findings correlate with the different expressions of the fluorangiographic features, which have been described as hypoperfusion, microneovascularisation, and anastomotic vessels vessels (Vannas 1969(Vannas , 1972Kottow 1979;Brooks & Gillies 1983. IICGA has been shown to improve the imaging of the iris vascular pattern in diabetic iridopathy and iris arteriovenous communications, thanks to a better penetration of the infrared wavelengths through the iris pigmentation, as well as a minimal dye-leakage in relation to the strong protein binding of the dye and the consequent large protein complex (Parodi et al 1995(Parodi et al , 1996(Parodi et al , 1998.…”
Section: Discussionmentioning
confidence: 93%
“…The iris vascular structure shows typical changes in PXS revealed by iris fluorescein angiography (IFA), such as hypoperfusion, microneovascularisation, and anastomotic vessels (Vannas 1969(Vannas , 1972Kottow 1979;Brooks & Gillies 1983.…”
mentioning
confidence: 99%
“…Iris involvement is histologically expressed by iris vasculopathy, with degeneration of smooth muscle cells, pericytes, and endothelial cells, pseudoexfoliation material deposits at the periphery of iris vessels, with thickening and reduplication of basement membranes. 1,2 The reported histological changes are the morphological correlate of the blood-aqueous barrier (BAB) breakdown, which can be studied by means of several techniques, including fluorophotometry, 3 laser flare-cell meter, [4][5][6] immunohistochemical tracer, 7 and iris angiography. 3,[8][9][10][11] Typical features of PES on iris angiography are hypoperfusion, microneovascularizations, and anastomotic vessels.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The reported histological changes are the morphological correlate of the blood-aqueous barrier (BAB) breakdown, which can be studied by means of several techniques, including fluorophotometry, 3 laser flare-cell meter, [4][5][6] immunohistochemical tracer, 7 and iris angiography. 3,[8][9][10][11] Typical features of PES on iris angiography are hypoperfusion, microneovascularizations, and anastomotic vessels. 3,[9][10][11] Comparison between iris fluorescein angiography (IFA) and iris indocyanine green angiography (IICGA) has shown that IICGA is superior in disclosing iris hypoperfusion and anastomotic vessels, whereas IFA allows a more precise detection of microneovascularizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation